The downfall of the gold standard - Cassel, Gustav (New York : A. M. Kelley, 1966)
The book examines the emergence of gold standard monetary system and its application in Great Britain and the international monetary system. It highlighted the problems that lead to the downfall of it.
First published in 1936.
Includes bibliographical footnotes and index
usc 15/09/2017
Loans
Keywords: Currency question; Gold standard; Gold